Amazing insects - Mound, L. A. (Laurence Alfred); Greenaway, Frank (New York : Distributed by Random House, 1993)
Text and photographs introduce the world of insects.
Includes index.
Booklist.
School Library Journal.
Wilson's Children.
5.1.
5.1
Keywords: Insects -- Juvenile literature; Insects; Insects